SURVEI MINAT SISWA TERHADAP OLAHRAGA BOLA VOLI DI SMP NEGERI 1 TIGA BINANGA KOTA TA 2024/2025 - Sahraygen Sembiring; Tri Widia Astuti Tamba; Aser Paul Nainggolan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted based on the importance of identifying students'interest in volleyball as one of the sports taught in Physical Education,Sports, and Health (PJOK). Interest is an essential factor influencingstudents' participation, enthusiasm, and achievement in both classroomlearning and extracurricular activities. The purpose of this study was todetermine the level of interest of eighthgrade students at SMP Negeri 1Siempat Teran, Karo Regency, in volleyball. This research employed aquantitative descriptive research method using a survey approach. Thepopulation consisted of all eighth-grade students of SMP Negeri 1 SiempatTeran, while the sample included 30 students selected through purposivesampling. The research instrument was a questionnaire consisting of 10statements with Yes/No response options. The validity test indicated that allquestionnaire items were valid, with the calculated correlation coefficient (rcount) exceeding the critical value (r table = 0.361), indicating that theinstrument was appropriate for data collection. Data were analyzed usingdescriptive statistical techniques in the form of percentages. The findingsrevealed that students' interest in volleyball varied across categories. Fourstudents (13.33%) showed a high level of interest, nine students (30%)demonstrated a moderate level of interest, and seventeen students(56.67%) had a low level of interest. Although all respondents understoodthe basic concept of volleyball (100%), their willingness to participate inintensive training and competitions remained relatively low. It can thereforebe concluded that, in general, the interest of eighth-grade students at SMPNegeri 1 Siempat Teran, Karo Regency, in volleyball is categorized as low.Therefore, Physical Education teachers and the school are expected toimprove students' interest by implementing more engaging learningmethods, providing adequate sports facilities, and organizing extracurricularactivities and competitions that encourage greater student participation involleyball.